CONTROLE DA ANTRACNOSE EM FEIJÃO COM PRODUTOS ALTERNATIVOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The use of resistance inducers that activate defense mechanisms of plants against pathogens can be a strategy for the management of diseases of cultivated plants. The objective of this work was to verify the efficiency of the alternative products in the activation of defense mechanisms in bean plants (Phaseolus vulgaris) and that result in the development of resistance to anthracnose (Colletotrichum lindemuthianum). The experimental design used for the experiments in detached leaf and greenhouse was the completely randomized with 9 treatments and 5 repetitions. The severity was assessed and the area below the anthracnose progress curve was calculated. The experiment was carried out in vitro in the laboratory and the rate of mycelial growth rate was calculated. The experimental design was completely randomized in factorial scheme 7 (products) X 4 (concentrations) with 5 replications. Experiments under field conditions were carried out in 2013/2014, 2014/2015 and 2015/2016 harvests at Fazenda Escola Capão da Onça. The experimental design was a randomized block design with 4 replications. The treatments used were: 1 - control; 2 - fentin hydroxide (Mertin 400 - 600 mL ha-1); 3 - Potassium phosphate (4.0 L ha-1); 4 - leaf fertilizar (Rocksil 2%); 5 - acibenzolar-S-methyl (Bion 500 WG - 25 g ha-1); 6 - Ascophyllum nodosum ( Acadian- 2 L ha-1); 7 - Bacillus subtilis (Serenade - 3.0 L ha-1) and 8 - Bacillus thuringiensis var. kurstaki (Dipel WP - 350 g ha-1). The assessment of the severity of anthracnose was conducted and the area under the curve of disease progression, the anthracnose index in the pods and yield components were calculated. Bacillus subtilis inhibited the growth of C. lindemuthianum in vitro. Bacillus thuringiensis and fungicide inhibited the growth of the pathogen at concentrations of 1000 and 100 ppm. The products of potassium phosphite, leaf fertilizer, acibenzolar-S-methyl and fungicide presented anthracnose control under greenhouse conditions. There was an increase in yield of the 2014/2015 harvest when fungicide treatments, Ascophyllum nodosum, leaf fertilizer and potassium phosphite were applied. In the crop of 2015/2016, fungicide and Bacillus thuringiensis were the treatments that caused an increase in productivity. The fungicide was the treatment that controlled the anthracnose in 2014/2015 and 2015/2016 harvests. In addition, in the 2015/2016 harvest, the alternative products potassium phosphite, Ascophyllum nodosum, Bacillus subtilis and Bacillus thuringiensis behaved similarly to the fungicide in the control of anthracnose in the upper third of the plants. x
Keywords: indução de resistência; Phaseolus vulgaris; Colletotrichum lindemuthianum; Induction of resistance; Phaseolus vulgaris; Colletotrichum lindemuthianum; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA